Magnetic resonance imaging plaque hemorrhage for risk stratification in carotid artery disease with moderate risk under current medical therapy - Hosseini, Akram A.; Simpson, Richard J.; Altaf, Nishath; Bath, Philip M.W.; MacSweeney, Shane T.; Auer, Dorothee P. (American Heart Association, 2017)
Background and Purpose—Magnetic resonance imaging (MRI)–defined carotid plaque hemorrhage (MRIPH) can predict recurrent cerebrovascular ischemic events in severe symptomatic carotid stenosis. It is less clear whether MRIPH can improve risk stratification despite optimized medical secondary prevention in those with moderate risk.